Oldest concrete vaulted and arch bridges in the Czech Republic – evaluation and preservation of their historical value - Roman Šafář; Vladislav Hrdoušek; Helena Včelová; Vendula Hlavničková (Acta Polytechnica CTU Proceedings, 2022)
The paper is related to a research project focused on tools for an evaluation and preservation of the historical value and function of arch and vaulted road bridges. It deals with the beginning of use of concrete vaulted and arch bridges in the area of the Czech Republic from the first structures built at the end of the 19th century up to the time just before the WWII. The paper includes examples of built structures as well as a general summary and development of the used technical solutions. Important part of the paper is a proposal of criterions for evaluation of their structural and historical value.